TINGKAT KEPERCAYAAN MASYARAKAT TERHADAP KULAWU TELLO DALAM MENGATASI KERABANG TELUR LUNAK DI KABUPATEN SIDENRENG RAPPANG - Ardi Salam; Nirmala Munir; Widya Fatika Sari; Takbir Mulawansyah; M. Fadhlirrahman Latief (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2021)
ABSTRACT Kulawu Tello is a stone that is believed by the community that come from inside the egg, usually this stone is used in the breeding of laying hens (layers) by breeders, especially in overcoming the problem of soft shelled egg. In this study aims to determine the effect of Kulawu Tello on the local community. The sample in this study was 78 people consisting of layer farmers who use and know about Kulawu Tello, local historians and the village head of Manisa Village. This research is descriptive, using a questionnaire to determine the level of trust of the Sidenreng Rappang community on the magical ability of Kulawu Tello in improving the performance of layers. The level of trust of each individual varies depending on how they believe in something according to what has been done. In general, people have high level of trust in the efficacy of Kulawu Tello stone because it has been used in their livestock business. It can be concluded that the level of public trust in Kulawu Tello in overcoming soft egg shells is very high, namely 52.56%, the percentage of moderate trust level is 21.38% and those who have a low level of trust are 5.13%. As for the level of public trust in Kulawu Tello in order to improving the performance of layers around 47.44%, the percentage of medium trust level around 26.49% and those who have a low level of trust around 4.27%. Keywords: belief, kulawu tello, magic, soft shelled egg.